2013
DOI: 10.4067/s0717-97072013000200016
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and Molecular Docking Studies on the Interaction of Dimetridazole With Human Serum Albumin

Abstract: Dimetridazole (DMZ) is widely used for the therapeutic treatment of farmed animals and is suspected of being human carcinogens and mutagens. The interaction between DMZ and human serum albumin (HSA) was investigated systematically by fluorescence spectroscopy, synchronous fluorescence, threedimensional fluorescence, CD spectroscopy, UV-vis absorption spectroscopy and molecular docking study. The results indicated that the probable quenching mechanism of HSA by DMZ was dynamic quenching. The corresponding therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…Several earlier studies have utilized spectroscopic techniques, particularly fluorescence spectral determination, to explore the different aspects of protein binding to various ligands [34][35][36]. Fluorescence quenching shows decline protein intrinsic fluorescence occurring through diverse molecular interactions [37,38]. The BSA fluorescence emission spectra with and without the addition of compound 3 were monitored in the wavelength range 290-500 nm upon excitation at 280 nm.…”
Section: Fluorescence Spectroscopic Investigation Of the Binding Mechmentioning
confidence: 99%
See 1 more Smart Citation
“…Several earlier studies have utilized spectroscopic techniques, particularly fluorescence spectral determination, to explore the different aspects of protein binding to various ligands [34][35][36]. Fluorescence quenching shows decline protein intrinsic fluorescence occurring through diverse molecular interactions [37,38]. The BSA fluorescence emission spectra with and without the addition of compound 3 were monitored in the wavelength range 290-500 nm upon excitation at 280 nm.…”
Section: Fluorescence Spectroscopic Investigation Of the Binding Mechmentioning
confidence: 99%
“…Therefore, in order to comprehensively elaborate the BSA binding sites for the compound 3 interaction, the BSA binding to possesses different fluorescence peaks, where peak 1 (λex 224 → λem 336) is controversial as numerous previous studies have claimed that it originated from the n → π* transition of the polypeptide backbone of the serum albumin structure, correlating its intensity to the BSA or HAS (Human Albumin Serum) secondary structures [38,52]. Conversely, in a latest multi-laboratory investigation reported by Bortolotti et al [53], it was established that this observed emission peak, following the excitation at 220-230 nm, aroused from Tyr and/or Trp.…”
Section: Site Markers Competitive Bindingmentioning
confidence: 99%
“…In the case of the Dmz ligand, the long wavelength absorption band was reported to fully overlap with the fluorescence band of tryptophan [19]. In the MD simulations, the Dmz ligand trapped by HSA is moving within the subdomain IIA, but never very away from the Trp214 chromophore fragment and close enough to provide MO overlap and allow for - stacking of the ligand with the chromophore (Fig 11).…”
Section: Dynamic Modelsmentioning
confidence: 95%
“…Tyr and the less intense La bands of Trp mainly contribute to the spectral region between 240-280 nm [16,17]. In contrast, the fluorescence maximum is due only to UV-excited Trp [18][19][20], but varies between 307 and 370 nm and in some cases even longer wavelengths depending on the microenvironment. In particular, the single Trp214 chromophore side residue is solely responsible for the longwavelength wing of the HSA (Trp214@HSA) spectrum starting from 300 nm (Figures 2 and 3) [19,21].…”
mentioning
confidence: 99%
See 1 more Smart Citation